Big Five personality characteristics are associated with depression subtypes and symptom dimensions of depression in older adults. (16th January 2017) - Koorevaar, A.M.L.; Hegeman, J.M.; Lamers, F.; Dhondt, A.D.F.; van der Mast, R.C.; Stek, M.L.; Comijs, H.C.
Abstract : Objective: This study examined the associations of personality characteristics with both subtypes and symptom dimensions of depression in older adults. Methods: Three hundred and seventy‐eight depressed older adults participated in the Netherlands Study of Depression in Older Persons. Personality characteristics were assessed by the NEO‐Five Factor Inventory. Subtypes and symptom dimensions of depression were determined using the Composite International Diagnostic Interview and the Inventory of Depressive Symptomatology (IDS). Multinomial logistic regression analyses were performed to examine the associations between personality and atypical, melancholic, and unspecified subtypes of major depression. Linear regression analyses examined the associations between personality and the IDS mood, somatic, and motivation symptom dimensions. The analyses were adjusted for confounders and additionally adjusted for depression severity. Results: Neuroticism, Extraversion, Conscientiousness, and Agreeableness were associated with specified (atypical or melancholic) major depression compared with unspecified major depression in the bivariate analyses but lost their significance after adjustments for functional limitations and severity of depression. Neuroticism was positively associated with the IDS mood and motivation symptom dimensions, also in the adjusted models. Further, Extraversion and Agreeableness were negatively associated with the IDS mood symptom dimension, and Extraversion and Conscientiousness were negatively associated with the IDS motivation symptom dimension. None was associated with the IDS somatic symptom dimension. Conclusions: This study demonstrated the association of personality characteristics with mood and motivational symptoms of late‐life depression. The lacking ability of personality to differentiate between melancholic and atypical depression seems to be largely explained by severity of depressive symptoms. Copyright © 2017 John Wiley & Sons, Ltd.